Dampak Pandemi Covid-19 Terhadap Permintaan Impor Karet Alam Indonesia di Negara Pengimpor Utama - Zainuddin Zainuddin (Jurnal MeA (Media Agribisnis), 2022)
Natural rubber is an important commodity in the manufacturing industry and world trade. Natural rubber as a primary commodity is traded in larger quantities than processed rubber products, but with a smaller value. Several countries have become Indonesian traditional natural rubber markets such as the United States, Japan and East Asian countries as well as European Union countries. The purpose of the study was to analyze the impact of the COVID-19 pandemic on Indonesia's natural rubber import demand in the United States, Japan and European Union (EU-28) markets. The analysis uses the Regression Discontinuity Design (RDD) model to describe the behavior and demand curve for Indonesia's natural rubber imports (especially TSNR) before and during the covid-19 pandemic. The impact of the covid-19 pandemic caused a discontinuity of the demand curve for natural rubber imports in the period before and during the pandemic at the Cut-off point. Based on the estimation results of the RDD model, the magnitude of the impact of the COVID-19 pandemic on the demand for Indonesian natural rubber in the main importing countries can be assessed. The results of the analysis show that the COVID-19 pandemic has reduced the number of requests for imports of natural rubber from Indonesia in the Japanese market by an average of 22.34 percent, the United States by 10.25 percent, and the EU-28 by 4.49 percent per month during the pandemic.